2022
DOI: 10.37796/2211-8039.1334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the analytical sensitivity and clinical performance of two cobas SARS-CoV-2 tests based on high-throughput and point-of-care systems

Abstract: Objectives This study examined analytical sensitivity, specificity, and the clinical performance in detecting SARS-CoV-2 of the Cobas SARS-CoV-2 Test based on the high-throughput Cobas 6800 system and the Cobas SARS-CoV-2 & Flu A/B Test based on the point-of-care cobas Liat system. Methods The commercial reagents containing SARS-CoV-2 RNA subgenomes were diluted for assessing the sensitivity of the RT-qPCR assay. 385 nasopharyngeal swab specimens taken from contacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, the Ct values of real-time RT-PCR were presented. The previous study revealed that cobas SARS-CoV-2 PCR test on the cobas 6800 system had a limit of detection of 25 to 50 copies/mL, which was also similar to the analytical sensitivity provided by the manufacturer's specification [ 23 , 24 ]. Finally, the performance of the VTRUST COVID-19 Antigen Rapid Test for detecting the SARS-CoV-2 Omicron variant was not known due to our study period being earlier than the emergence of Omicron variant, which needs to be validated in the further study.…”
Section: Discussionmentioning
confidence: 59%
“…However, the Ct values of real-time RT-PCR were presented. The previous study revealed that cobas SARS-CoV-2 PCR test on the cobas 6800 system had a limit of detection of 25 to 50 copies/mL, which was also similar to the analytical sensitivity provided by the manufacturer's specification [ 23 , 24 ]. Finally, the performance of the VTRUST COVID-19 Antigen Rapid Test for detecting the SARS-CoV-2 Omicron variant was not known due to our study period being earlier than the emergence of Omicron variant, which needs to be validated in the further study.…”
Section: Discussionmentioning
confidence: 59%
“…Focusing on the cause of the spontaneous testicular hematoma, the patient denied any recent trauma, sexual activity, or other possible medical interventions that could cause a hematoma. CT scans did not reveal any other possible secondary causes of his hematoma [ 17 , 18 ]. Reviewing the patient’s clinical course, we paid close attention to his underlying reactive arthritis and medication use.…”
Section: Discussionmentioning
confidence: 99%
“…In our hospitals, the cobas ® Liat ® system (Roche, Penzberg, Germany), a small instrument for automated RT-PCR testing with a short turnaround time of less than 30 min, has been selected as the primary SARS-CoV-2 screening tool for ED patients [ 15 ]. However, due to a significant number of false-positive results during assay validation, it was determined that any positive Liat ® result has to be confirmed via RT-PCR for the final diagnostic report, in accordance with the 2021 FDA communication [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%